2016
DOI: 10.1177/1077558716677826
|View full text |Cite
|
Sign up to set email alerts
|

To What Extent Are State Scope of Practice Laws Related to Nurse Practitioners’ Day-to-Day Practice Autonomy?

Abstract: We explore the extent to which state scope of practice laws are related to nurse practitioners (NPs)' day-to-day practice autonomy. We found that NPs experienced greater day-to-day practice autonomy when they had prescriptive independence. Surprisingly, there were only small and largely insignificant differences in day-to-day practice autonomy between NPs in fully restricted states and those in states with independent practice but restricted prescription authority. The scope of practice effects were strong for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 26 publications
(38 reference statements)
4
32
0
Order By: Relevance
“…The interviews revealed that health care organizations are still learning how to manage their increasingly diversified clinical staff and are open to learning better practices. This is consistent with a growing body of research showing that organizational practices are key to determining how APCs are used (Park et al, 2018; Park et al, 2020; Pittman et al, 2018; Poghosyan, Nannini, Smaldone, et al, 2013, Poghosyan, Nannini, Stone, et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The interviews revealed that health care organizations are still learning how to manage their increasingly diversified clinical staff and are open to learning better practices. This is consistent with a growing body of research showing that organizational practices are key to determining how APCs are used (Park et al, 2018; Park et al, 2020; Pittman et al, 2018; Poghosyan, Nannini, Smaldone, et al, 2013, Poghosyan, Nannini, Stone, et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…Research has shown that organizational factors matter more than the SOP regulations in both hospitals (Pittman et al, 2018), and in CHCs (Park et al, 2020). This is consistent with an increasingly strong theme emerging from recent research that organizational policies are essential to how NPs and PAs are utilized (Park et al, 2018; Poghosyan, Nannini, Smaldone, et al, 2013, Poghosyan, Nannini, Stone, et al, 2013).…”
Section: Conceptual Frameworksupporting
confidence: 87%
“…The rate of incident billing was lower in these states compared to states with reduced or restricted NP practice authority. 31 We found consistent results. Third, we were unable to calculate patient panel size due to the limitation that the data is a 5% random sample, which would otherwise provide a more thorough picture of the capacity of the primary care model.…”
Section: Discussionsupporting
confidence: 80%
“…The APN role implementation is complex and requires prior planning in order to introduce the role and clarify the difference between their role and other professionals. Removing the barriers that prevent APNs from practicing to their full scope is very important to expand services of PHC and to make them more effective and efficient providers of care (Park et al, 2016). Whittemore and Knafl's (2005) integrative review framework was chosen to guide this review.…”
Section: Introductionmentioning
confidence: 99%